Simulation of Cathodic Protection System Using Matlab - A. Al Habobi, Naseer; F. Abed, Shahad (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
Iraq has a huge network of pipelines, transport crude oil and final hydrocarbon products as well as portable water. These networks are exposed to extensive damage due to the underground corrosion processes unless suitable protection techniques are used. In this paper we collect the information of cathodic protection for pipeline in practical fields (Oil Group in Al Doura), to obtain data base to understand and optimize the design which is made by simulation for the environmental factors and cathodic protection variables also soil resistivity using wenner four terminal methods for survey sites; and soil pH investigations were recorded for these selected fields were within 7-8, and recording the anodes voltage and its related currents for the protection of underground pipelines.Modeling enables the designer to build cathodic protection for buried structure and predicting the places of anodes sites and its operating voltages and currents under various operational conditions, and comparing it with those in practices. In this work we compared between the field and simulation results which include, anode numbers, rectifier voltage, rectifier current and anode resistance. The most economical design for the first pipeline was at station no. 2 which need 2.5 A for protection of the pipeline for that specific length and for second pipeline station no. 4 which need 12 A for protection of the pipeline for that specific length.